2017
DOI: 10.1002/cm.21377
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA helicase, RuvBL1 and its Chlamydomonas homologue, CrRuvBL1 plays an important role in ciliogenesis

Abstract: Several nuclear and nucleic acid-binding proteins were detected in the proteomic analyses of ciliary fractions from various organisms. Yet very little is known about the role of these proteins in ciliogenesis and ciliary signaling. In an attempt to characterize the role of these nuclear proteins, we identified a hypothetical protein from Chlamydomonas reinhardtii, CrRuvBL1, which is homologous to human DNA helicase, HsRuvBL1. CrRuvBL1 localizes to flagella and nucleus in vegetative Chlamydomonas cells. It accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Immunofluorescence analysis of mouse ependymal and oviduct epithelial multiciliated cells, as well as studies of Kupffer's vesicle and pronephric ciliated cells in zebrafish, showed that RuvBL1 was present in the cytoplasm [15,49] and in the nucleus [49]. Contradictory to these data, using a non-commercial antibody, it was shown that in Chlamydomonas RuvBL1 was also present in flagella [50].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 96%
“…Immunofluorescence analysis of mouse ependymal and oviduct epithelial multiciliated cells, as well as studies of Kupffer's vesicle and pronephric ciliated cells in zebrafish, showed that RuvBL1 was present in the cytoplasm [15,49] and in the nucleus [49]. Contradictory to these data, using a non-commercial antibody, it was shown that in Chlamydomonas RuvBL1 was also present in flagella [50].…”
Section: R2tp Complexes In the Dynein Arm Assemblymentioning
confidence: 96%
“…RuvB-like DNA helicases have been well studied in bacteria ( Iwasaki et al, 1992 ; Shinagawa et al, 1991 ; Yamada et al, 2001 ). In eukaryotes, the proteins RuvB-like 1 and RuvB-like 2 are also called pontin and reptin ( Jha and Dutta, 2009 ), respectively, and they have acquired additional functions including DNA repair and chromatin remodelling ( Dauden et al, 2021 ; Tammana and Tammana, 2017 ). A chromatin remodelling complex from T. brucei , which contains TbRuvBL1 and TbRuvBL2, has been described recently ( Vellmer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…RuvB-like DNA helicases have been well studied in bacteria (Shinagawa, 1991;Iwasaki, 1992;Yamada, 2001). In eukaryotes, the proteins RuvB-like 1 and RuvBlike 2 are also called pontin and reptin (Jha, 2009), respectively, and they have acquired additional functions including DNA repair and chromatin remodeling (Tammana, 2017;Dauden, 2021). A chromatin remodelling complex from T. brucei, which contains TbRuvBL1 and TbRuvBL2, has been described recently (Vellmer, 2022).There is to our knowledge only one experimental study from trypanosomatids, where LmRUVBL1 and LmRUVBL2 from Leishmania major were recombinantly (co-)expressed.…”
Section: Discussionmentioning
confidence: 99%